A Secure Image Transmission Scheme Based on Improved DCSK - Lifang He; Gang Zhang; Tianqi Zhang (Dianxin kexue)
Non-coherent demodulation technology is applied in the differential chaos shift keying（DCSK）and it's unnecessary for the receiver to generate chaotic synchronous signals at the receiving end. The structure in DCSK is simple and has good performance in anti-noise. However, it is lack of performance in security, and easier to be cracked. A modified DCSK scheme was proposed for the security problems caused by the traditional DCSK scheme. It retains the good performance of the old one and greatly increases security performance at the same time. The theoretical analysis toward the system was deeply carried out. The relationship among the BER, the frequency spread factor and SNR were also deeply analyzed. Finally, it was applied in an image transmission system as an example. The simulation results indicate that the performance of the bit error ratio（BER）and security are greatly improved. The feasibility was also proved by simulations.